About the Use of Generalized Forms of Derivatives in the Study of Electromagnetic Problems - Giulio Antonini; Giuseppe Dattoli; Fabrizio Frezza; Silvia Licciardi; Fabrizio Loreto (Applied Sciences, 2021)
The use of non-local operators, defining Riemann–Liouville or Caputo derivatives, is a very useful tool to study problems involving non-conventional diffusion problems. The case of electric circuits, ruled by non-integer derivatives or capacitors with fractional dielectric permittivity, is a fairly natural frame of relevant applications. We use techniques, involving generalized exponential operators, to obtain suitable solutions for this type of problems and eventually discuss specific problems in applications.